Study on the Color Genesis of South Red Agate and the Geological Characteristics of the Siliceous Gravel Layer - Kongliang Li; Ye Yuan (Journal of Chemistry)
The aim of the study was to explore the gem mineralogical characteristics of southern red agate and then analyze its structural characteristics and color causes. The mineral composition, structure, and chromogenic minerals of Nanhong agate were tested by a conventional gemmological test and observed under the microscope, infrared spectrum, and microlaser Raman spectrum. It is found that the color of southern red agate samples is mainly dark red or orange red, and colorless, white or yellow bands can be seen in some samples; the relative density is in the range of 2.59∼2.65. The matrix structure of the sample is mainly long fiber and short fiber, and some of them are fine-grained and crystalline plasmid. There are concentric ring-banded structures, and some horizontal banded and vein structures can also be seen. The analysis and test results show that the south red agate has a typical radial fiber structure, and the main chemical component is SiO2; Under the orthogonal polarizing microscope, a large number of round reddish brown mineral inclusions with banded distribution can be seen, the spot-colored mineral is iron oxide hematite, and calcite of the late hydrothermal origin can be seen in the cracks. In addition, the study shows that the formation of south red agate is multistage and the formation of hematite inclusions is also multistage.